2016
DOI: 10.1155/2016/1360386
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Directional Immunomodulatory Effects of Corbrin Capsule on Autoimmune Thyroid Diseases

Abstract: Purpose. To investigate the effects of Corbrin Capsule (CS-C-Q80), a drug derived from Cordyceps sinensis (Berk.) Sacc., on autoimmune thyroid diseases (AITD). Methods. 44 Patients with Graves's disease (GD) and 56 patients with Hashimoto's thyroiditis (HT) were randomly assigned to treatment group (GD-Tx and HT-Tx) or control group (GD-Ct and HT-Ct). The control groups were given methimazole or levothyroxine only while the treatment groups were given Corbrin Capsule (2.0 g tid) besides the same conventional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A total of 1014 HT patients were included in the 14 RCTs, including 339 patients with normal thyroid function and 675 patients with hypothyroidism. These trials were conducted in mainland China from 2015 to 2021, of which 13 were published in Chinese ( Zhang, 2015 ; Aisha, 2016 ; Li, 2017 ; Yang et al, 2018a ; Yang et al, 2018b ; Kang and Piao, 2019 ; Bai et al, 2020 ; Jin and Wang, 2020 ; Zhu et al, 2020 ; Tan, 2021 ; Wang et al, 2021 ; Xue et al, 2021 ; Zhan and Chen, 2021 ) and one in English ( He et al, 2016 ). There were 523 and 491 patients in the experimental and control groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1014 HT patients were included in the 14 RCTs, including 339 patients with normal thyroid function and 675 patients with hypothyroidism. These trials were conducted in mainland China from 2015 to 2021, of which 13 were published in Chinese ( Zhang, 2015 ; Aisha, 2016 ; Li, 2017 ; Yang et al, 2018a ; Yang et al, 2018b ; Kang and Piao, 2019 ; Bai et al, 2020 ; Jin and Wang, 2020 ; Zhu et al, 2020 ; Tan, 2021 ; Wang et al, 2021 ; Xue et al, 2021 ; Zhan and Chen, 2021 ) and one in English ( He et al, 2016 ). There were 523 and 491 patients in the experimental and control groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5 RCTs compared OS preparations combined with a low-iodine diet to a low-iodine diet, of which 4 RCTs investigated Bailing capsule ( Zhang, 2015 ; Li, 2017 ; Zhu et al, 2020 ; Xue et al, 2021 ) and one RCT investigated Jinshuibao capsule ( Tan, 2021 ). 9 RCTs compared OS preparations combined with LT4 to LT4, of which 7 RCTs investigated Bailing capsule ( Aisha, 2016 ; He et al, 2016 ; Yang et al, 2018a ; Yang et al, 2018b ; Jin and Wang, 2020 ; Wang et al, 2021 ; Zhan and Chen, 2021 ) and 2 RCTs investigated Jinshuibao capsule ( Kang and Piao, 2019 ; Bai et al, 2020 ). The basic characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for the controversy over the pharmacological effect of HS is the lack of knowledge of the active constituents. Some constituents have been reported in HS, such as cordycepin (3′-deoxyadenosine), cordycepic acid (d-mannitol), polysaccharides, and amino acids [25, 26]. However, the pharmacological effects of these constituents have been considered limited for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Hirsutella sinensis (HS), an anamorph of CS [23], has been artificially cultured on a large scale [24]. The bioactivity of HS is similar to CS because of their analogous composition [25, 26]. HS has been shown to have therapeutic effects on renal function damage by aristolochic acid [27].…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] It is composed of Cordyceps mycelium, which is rich in a variety of trace elements, amino acids, adenosine, and cordycepin to improve blood circulation, inhibit neurotransmitter release and regulate adenylate cyclase activity. Studies have shown that BC could regulate human immune function, [11][12][13] repair renal tubular epithelial cells, prevent renal tubular atrophy, and reduce kidney damage to improve renal function. [14,15] Our group tried to use the combination of BC and KA to treat CKD patients, and we preliminarily found the therapy could improve the symptoms of fatigue and dizziness to improve the quality of life.…”
Section: Introductionmentioning
confidence: 99%